Cerebral blood flow changes associated with attribution of emotional valence to pleasant, unpleasant, and neutral visual stimuli in a PET study of normal subjects. - Paradiso, Sergio; Johnson, Debra L.; Andreasen, Nancy C. (American Journal of Psychiatry, 1999)
|WbObjective:[|WB] To assist in the development of a model for the psychopathology of emotions, the present study sought to identify the neural circuits associated with the evaluation of visual stimuli for emotional valence. |WbMethod:[|WB] Seventeen healthy individuals were shown three sets of emotionally laden pictures carrying pleasant, unpleasant, and neutral content. While subjects evaluated the picture set for emotional valence, regional cerebral blood flow was measured with the use of {15O} water positron emission tomography. Subjective ratings of the emotional valence of the picture sets were recorded. Data were analyzed by comparing the images acquired during the neutral condition with the unpleasant and pleasant image sets and the unpleasant and pleasant conditions with each other. |WbResults:[|WB] Processing of pleasant stimuli was associated with increased blood flow in the dorsal-lateral, orbital, and medial frontal cortex relative to the unpleasant condition and in the cingulate, precuneus, and visual cortex relative to the neutral condition. Evaluation of unpleasant stimuli activated the amygdala, visual cortex, and cerebellum relative to the pleasant condition and the nucleus accumbens, precuneus, and visual cortex relative to the neutral condition. |WbConclusions:[|WB] Observing and assigning emotional value to unpleasant stimuli produced activations in subcortical limbic regions, whereas evaluation of pleasant stimuli produced activations in cortical limbic areas. These findings are consistent with the notion of a subcortical and archaic danger recognition system and a system detecting pleasantness in events and situations that is phylogenetically younger, involving primarily the prefrontal cortex. Reprinted by permission of the publisher.